Variation in STAT4 is associated with systemic lupus erythematosus in a Finnish family cohort. Issue 5 (27th August 2009) - Hellquist, Anna; Sandling, Johanna K; Zucchelli, Marco; Koskenmies, Sari; Julkunen, Heikki; D'Amato, Mauro; Garnier, Sophie; Syvänen, Ann-Christine; Kere, Juha
Abstract : Objectives: To investigate whether 10 single nucleotide polymorphisms (SNPs) and haplotypes in the STAT4 gene, previously associated with systemic lupus erythematosus (SLE) in a Swedish case–control cohort, are also associated with SLE risk in a Finnish SLE family cohort. Method: Genotyping was performed in 192 Finnish families, with 237 affected subjects and their healthy relatives, using the SNPstream genotyping system. Results: Transmission disequilibrium test analysis provided the strongest signal of association for two linked SNPs: rs7582694 (p=0.002, OR=2.57) and rs10181656 (p=0.001, OR=2.53). Haplotype association analysis using a sliding window approach was also performed and showed that the strongest association signal originates from SNPs in intron 3 of STAT4 . Conclusion: The main association signal for STAT4 with SLE previously reported in Caucasians is the same in the Finnish population. This is the first study that confirms the association of STAT4 with SLE in a family cohort.